Macroscopic Features of the Intugementary System of Geriatric Kintamani Dogs - Ni Putu Anggita Indrayani; I Nengah Wandia; I Wayan Nico Fajar Gunawan; Putu Devi Jayanti (Media Kedokteran Hewan)
Observing the health of Kintamani dogs, especially at geriatric age, is important as an effort to preserve their lives. Observations of the integumentary system can provide information related to clinical animal health. This study aims to determine the integumentary condition of Kintamani dogs macroscopically at geriatric age. This study used 5 Kintamani dogs of geriatric age with a healthy clinical condition. The research procedure was carried out by macroscopic observation of hair and skin by inspection and palpation methods. The results showed that the hair of geriatric dog samples experienced changes in color and texture when compared to productive age Kintamani dogs. Observation of skin flexibility showed that the skin flexibility of geriatric dogs was lower when compared to productive-age Kintamani dogs. Observations of the hair strength of Kintamani dogs showed that at the average geriatric age it was difficult to pull out during manual combing with the observer's hand.  This observation shows that the integumentary system of geriatric Kintamani dogs is macroscopically not much different from productive-age Kintamani dogs.